2019
DOI: 10.3389/frobt.2019.00013
|View full text |Cite
|
Sign up to set email alerts
|

User Centered Design of Interaction Techniques for VR-Based Automotive Design Reviews

Abstract: The exterior design is one of the most important selling propositions in the automotive premium market. Because of progressing digitization in the automotive industry, it is increasingly assessed using virtual 3D models. In this context, Virtual Reality (VR) is a key technology of continuously growing importance. However, complicated interaction in VR proves to be a major drawback in industrial settings. In this paper, we report insights of our user centered approach aiming at appropriate VR interaction techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Figure 4 shows the distribution of papers in each category. The automotive industry was the subject of seven articles (37%) [43,46,48,50,52,54,55] It was expected that a substantial number of virtual reality studies would be conducted in the vehicle industry. These findings are congruent with those of [56].…”
Section: Application Fields and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 4 shows the distribution of papers in each category. The automotive industry was the subject of seven articles (37%) [43,46,48,50,52,54,55] It was expected that a substantial number of virtual reality studies would be conducted in the vehicle industry. These findings are congruent with those of [56].…”
Section: Application Fields and Methodsmentioning
confidence: 99%
“…The importanc of the automobile industry may be related to the fact that virtual technologies have long been utilized in this sector in a range of specialties and applications, such as manufactur ing, training, and maintenance, to mention a few [13,57,58]. Departments such as design engineering, maintenance, and assembly are already using the technology to suppor The automotive industry was the subject of seven articles (37%) [43,46,48,50,52,54,55]. It was expected that a substantial number of virtual reality studies would be conducted in the vehicle industry.…”
Section: Application Fields and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding virtual reality, it has been demonstrated that, by optimizing the virtual environment's architecture, the use of UCD in the development of virtual experiences offers a more efficient, satisfying, user-friendly experience (Gabbard et al, 1999;Jerald, 2015;Barbieri et al, 2018;Gladden, 2018). It has been employed to design and evaluate virtual experiences in museums (Barbieri et al, 2018), tourism (Poux et al, 2020), automotive industries (de Clerk et al, 2019), and military (Hix et al, 1999), and medical fields (Vailland et al, 2019). Furthermore, it has been used to develop virtual reality content for mental health (Fidopiastis et al, 2010;Koenig et al, 2012;Boger et al, 2018;Eisapour et al, 2018;Flobak et al, 2019;Pizzoli et al, 2019), particularly virtual environments for cognitive assessment and rehabilitation (Fidopiastis et al, 2010;Koenig et al, 2012), and to promote physical activity among people with mild cognitive impairment (MCI) (Boger et al, 2018;Eisapour et al, 2018).…”
Section: Development and Evaluation Protocol Of The Mind-vr Psychoeducational Virtual Experiencementioning
confidence: 99%